A SYSTEMATIC REVIEW ON THE ROLE OF GUT MICROBIOTA IN NUTRITION AND HEALTH (Journal of Medical & Health Sciences Review, 2026)
The gut microbiota, a diverse community of trillions of microorganisms residing in the human gastrointestinal tract, plays a pivotal role in maintaining host nutrition, immunity, and metabolic function. Emerging research highlights its significant influence on the development and progression of various diseases, including obesity, type 2 diabetes, inflammatory bowel disease (IBD), and neuropsychiatric disorders. This narrative review aimed to synthesize recent findings (2020–2025) on the relationship between gut microbiota, diet, and health outcomes. A comprehensive search of databases such as PubMed, Scopus, and Google Scholar identified 110 peer-reviewed studies examining the functional roles of gut microbes, dietary interventions, and therapeutic strategies. The findings emphasize that microbial diversity and composition are influenced by factors such as diet, age, medication, birth mode, and lifestyle. High-Fiber diets, such as the Mediterranean diet, promote beneficial microbes like Bifidobacterium and Lactobacillus, while Western diets are associated with dysbiosis and chronic inflammation. Therapeutic approaches including probiotics, prebiotics, synbiotics, and faecal microbiota transplantation (FMT) demonstrated varying success in modulating gut flora to improve health. Dysbiosis was notably linked to metabolic disorders, cognitive decline, immune dysfunction, and gastrointestinal diseases. In conclusion, the gut microbiota acts as a key mediator between diet and health, influencing disease onset and therapeutic response. Personalized nutrition, combined with targeted microbial modulation, offers promising avenues for disease prevention and management. Future research should focus on standardized methods, long-term clinical trials, and multi-omics approaches to unlock the full therapeutic potential of the gut microbiome.